RANCANG BANGUN SISTEM INFORMASI PELAYANAN PENGADUAN MASYARAKAT BERBASIS WEB PADA DESA SUKADAMAI KABUPATEN TANGERANG - Rohmat Taufik; Fauyhi Eko Nugroho (Jurnal Dinamika UMT, 2021)
ABSTRACT Public Complaints are information or notifications submitted by the public, public complaints containing complaints and or dissatisfaction related to the behavior and or implementation of duties and functions of government employees, which are carried out by government employees, and or information about alleged violations of the code of ethics or employee discipline committed by employees. government. Currently, the Sukadamai village office is still using the existing complaint contact, this is considered ineffective because the process is long so that the complaint is not immediately resolved, and the recording of complaint reports that still use paper is very at risk of being lost or damaged and it will take more time to find the complaint file. when needed. Therefore, researchers researched to analyze the current process and design an information system for Community Complaints Services to collect data, researchers conducted observations, surveys, and interviews at the Sukadamai Village Office. In the design of information systems, researchers use the UML (Unified Modeling Language) method to design the system to be built. Researchers hope that the designed information system can be used as a reference in the system development process in the future.